Argentine Ethnobiology: A Future in Peril - Rico Lenta, Catalina; Grimaldi, Pablo Andrés; Ladio, Ana H. (Ethnobiology and Conservation, 2024)
Based on an online survey and a workshop with young ethnobiologists, we analyze the current state and future prospects of the discipline in Argentina. The research topic analysis, geographic distribution, and insights into participant motivations and challenges highlight concerns regarding professional development in the context of underfunding and science devaluation within the country. We propose strategies for strengthening the field, including increased networking and improved representation in university curricula.